Analisis Konten Nilai-Nilai Kebangsaan dan Multikultural dalam Buku Teks PKn - Bakar, Abu (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to analyze the representation of national and multicultural values in Civic Education (PKn) textbooks for Elementary Schools (SD) and identify gaps and biases in their content presentation. The research method employed is qualitative library research, with the research subjects being PKn textbooks for grades IV-VI under the 2013 Curriculum and Merdeka Curriculum, while the research objects include textual content, images, and learning activities. Data collection was conducted through documentary study, and data analysis utilized Krippendorff's content analysis model with stages of unitization, categorization, and interpretation. The results indicate that national values dominate (70%) with a rote-learning approach, while multicultural values (30%) remain limited and superficial, particularly in the representation of minority groups and gender equality. Furthermore, the integration between national and multicultural concepts is not yet optimal. The study concludes that improvements to PKn SD textbooks are needed by incorporating more concrete multicultural examples, inclusive representation, and interactive learning approaches to strengthen students' understanding of diversity within the framework of national unity.